Integrated genomic analysis to reduce chromosomal analysis for the diagnosis of pediatric hematologic malignancies: addressing the shortage of cytogenetic technologists - Dong Li; Sarah K. Tasian; Gerald Wertheim; Susan R. Rheingold; Kathrin M. Bernt; Haley Newman; Luanne Wainwright; Donna M. Wilmoth; Brian Thiel; Lea F. Surrey; Elizabeth Margolskee; Vinodh Pillai; et al. (Haematologica)
Not available.